2022
DOI: 10.1186/s11658-022-00381-1
|View full text |Cite
|
Sign up to set email alerts
|

5-Methoxyflavone-induced AMPKα activation inhibits NF-κB and P38 MAPK signaling to attenuate influenza A virus-mediated inflammation and lung injury in vitro and in vivo

Abstract: Influenza-related acute lung injury (ALI) is a life-threatening condition that results mostly from uncontrolled replication of influenza virus (IV) and severe proinflammatory responses. The methoxy flavonoid compound 5-methoxyflavone (5-MF) is believed to have superior biological activity in the treatment of cancer. However, the effects and underlying mechanism of 5-MF on IV-mediated ALI are still unclear. Here, we showed that 5-MF significantly improved the survival of mice with lethal IV infection and amelio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Indeed, recent studies have demonstrated that infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can induce the activation of p38/MAPK, resulting in an upregulation of proinflammatory cytokines and an enhanced replication of the virus ( Bouhaddou et al, 2020 ). It has been observed that inhibiting the p38/MAPK signaling pathway can effectively mitigate the Influenza virus (IV) replication and the excessive production of proinflammatory mediators ( Yang et al, 2022 ). Additionally, the infection of Newcastle Disease Virus (NDV) has been shown to induce the activation of p38/MAPK/Mnk1 signaling, facilitating the efficient synthesis of viral proteins ( Zhan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies have demonstrated that infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can induce the activation of p38/MAPK, resulting in an upregulation of proinflammatory cytokines and an enhanced replication of the virus ( Bouhaddou et al, 2020 ). It has been observed that inhibiting the p38/MAPK signaling pathway can effectively mitigate the Influenza virus (IV) replication and the excessive production of proinflammatory mediators ( Yang et al, 2022 ). Additionally, the infection of Newcastle Disease Virus (NDV) has been shown to induce the activation of p38/MAPK/Mnk1 signaling, facilitating the efficient synthesis of viral proteins ( Zhan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…IAV increased glycolysis to promote viral replication by inducing HIF-1 stabilization, transcription, translation, and activation [ 64 ]. MAPK and autophagy signaling pathways contributed to IAV virus-induced inflammation and lung injury [ 65 , 66 ]. FOXO signaling pathway has also been showed playing an important role in the IAV-induced alveolar macrophage dysfunction [ 67 ], and FoxO1 negatively regulated cellular antiviral response by promoting degradation of IRF3 [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these differential expression patterns were consistent with the RNA-seq results. Five of our screened DEGS have been reported to affect influenza virus replication in host cells: TLR2, IFIT5, and RSAD2 have been reported to inhibit replication, while HCLS1 and AP2B1 have been shown to promote replication [13][14][15][16][17]. The remaining 13 screened DEGs have also been shown to play an important role in a variety of viruses.…”
Section: Verification Of Mrna Expression Of 18 Screened Degsmentioning
confidence: 98%
“…For example, the SARS-CoV-2 envelope (E) protein has been shown to specifically interact with the TLR2 receptor, which in turn plays its antiviral role by activating the NF-κB transcription factor and stimulating the production of the inflammatory chemokine CXCL8 [12]. In addition, some studies have shown that TLR2, IFIT5, RSAD2, CLDN1, and HCLS1 play an important role in regulating the replication of influenza and other viruses in host cells [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%